2014
DOI: 10.1590/s1415-43662014000600002
|View full text |Cite
|
Sign up to set email alerts
|

Componentes de produção, produtividade e eficiência da irrigação do feijão-caupi no cerrado de Roraima

Abstract: R E S U M ONeste trabalho objetivou-se avaliar os componentes de produção, produtividade e eficiência da irrigação do feijão-caupi em lâminas de irrigação no cerrado de Roraima. Conduziu-se o experimento no Campo experimental Água Boa, da Embrapa Roraima, em cultivo sobre palhada sob irrigação por aspersão convencional, de fevereiro a abril e de setembro a novembro de 2012. Foram testadas cinco lâminas de irrigação 30, 60, 90, 120 e 150% da evapotranspiração de referência (ETo) e três cultivares de caupi: BRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
18
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 14 publications
(5 reference statements)
9
18
0
16
Order By: Relevance
“…4B). These results bear close similarity to those of Torres et al (2013) and Locatelli (2014) who recorded the highest NG when the water supplied was 115 and 108% of field capacity, respectively. At the 150% irrigation level the water consumption was observed to reach its peak (38.5 L per pot).…”
Section: Number Of Grainssupporting
confidence: 91%
See 1 more Smart Citation
“…4B). These results bear close similarity to those of Torres et al (2013) and Locatelli (2014) who recorded the highest NG when the water supplied was 115 and 108% of field capacity, respectively. At the 150% irrigation level the water consumption was observed to reach its peak (38.5 L per pot).…”
Section: Number Of Grainssupporting
confidence: 91%
“…3B). The results from the present study were almost similar to the findings of Locatelli (2014), who confirmed maximum grain yield at 94% irrigation levels in cowpea (Vigna unguiculata).…”
Section: Mass Of 100 Grains and Grain Productionsupporting
confidence: 91%
“…When the irrigation is well conducted, it increases both cowpea yield and grain quality (Oliveira et al 2011, Silva et al 2013and 2016, Locatelli et al 2014. Silva et al (2016) evaluated 20 genotypes under irrigation and observed an average grain yield 27 % higher than the same genotypes under no irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de a maior área cultivada com feijão esteja situada na região nordeste, a produtividade média (470 kg ha -1 ) ainda é inferior às demais regiões do Brasil (CONAB, 2017). Para elevar esta baixa produtividade, novas tecnologias veem sendo utilizadas; dentre elas, o uso da irrigação, que proporciona maior rendimento associado a melhor qualidade e maior valor comercial (LOCATELLI et al, 2014).…”
Section: Introductionunclassified